2015
DOI: 10.4103/1357-6283.161851
|View full text |Cite
|
Sign up to set email alerts
|

Development of active learning modules in pharmacology for small group teaching

Abstract: In this study, students preferred an active learning environment, though to pass examinations, they preferred the tutorial mode of teaching. Further efforts are required to explore the effects on learning of introducing similar modules for other topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…Ghosh and Dawka showed that 80 % of students like a judicious mixture of the didactic lecture and problem based learning [15]. In one of the studies, although most students admitted that case-based interactive sessions enhance their understanding and aroused intellectual curiosity, they preferred tutorials to help them score better in the examinations [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh and Dawka showed that 80 % of students like a judicious mixture of the didactic lecture and problem based learning [15]. In one of the studies, although most students admitted that case-based interactive sessions enhance their understanding and aroused intellectual curiosity, they preferred tutorials to help them score better in the examinations [16].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Students are taught how to successfully write prescriptions for a medical ailment, but they are not adequately trained to counsel or educate patients regarding their proper use, which in turn may affect treatment outcomes. For imbibing and enhancing communication skills, interactive and innovative tools are preferred over pure didactic methods.…”
mentioning
confidence: 99%
“…The evaluation, which was based on a checklist prepared, using the modified Calgary-Cambridge guide, showed a significant improvement in the posttraining scores. In view of these and findings of other studies,[567] the researchers planned the current study to explore the students’ view points of the role-play and also to ascertain if learning communication skills was a felt need by students for their future clinical practice.…”
mentioning
confidence: 99%
“…There have been various modules developed, such as online learning modules (Aziz & Lee, 2017), mathematics (material) modules (Hudson et al, 2018;Newton, Gale, Alemdar, & Wind, 2018), active learning modules (Tripathi, Sarkate, Jalgaonkar, & Rege, 2015), yet there is no mathematics learning strategy module. The most related one is a study conducted by Peniati(2012) which develop module of science learning strategy based on research result.…”
Section: Introductionmentioning
confidence: 99%